Evaluation of the Dynamic Characteristics of AZ91D Crankcase Covers and Boxes - Zhang, L.; Shang, H.C.; Zhao, Z.Q.; Zhang, D.F. (Проблемы прочности, 2015)
Dynamic tests are performed on similarly structured crankcase covers and boxes made of AZ91D magnesium and A380 aluminum alloys. The real vibration and noise control effect of an AZ91D magnesium alloy is evaluated, based on the behavior of the integral frequency response function, which is derived from the measured surface vibrations of the crankcase cover under operating conditions. The results indicate that crankcase covers and boxes made of AZ91D magnesium and A380 aluminum alloys with the same geometry possess similar normal characteristics. Both materials are interchangeable. However, the stiffness of AZ91D crankcase covers and boxes is poor. It is also difficult to obtain good engineering vibration and noise effects in the real structure due to an AZ91D high damping capacity. At the same excitation and frequency response at different structure characteristics, the measurement analysis of time-domain response indicates that methods to strengthen the crankcase box stiffness, such as embedding a main bearing steel sleeve, is favorable for improving the dynamic characteristics of an AZ91D crankcase box.